Online Learning Course Amid Outbreaks: A Comparison of Satisfaction Between Islamic High School and High School Students - Ahmad Juhaidi; Noor Hidayati; Maulida Rezkia; Hamdani; Ahmad Wafa Nizami (Jayapangus Press, 2023)
Amid outbreaks, with limited preparation and infrastructure, learning is carried out by all of school in Indonesia. This research is aimed to investigate the satisfaction of Islamic high school (IHS) and high school (HS) students with online learning that they have participated in during the pandemic. This research is quantitative research. Data was collected by online questionnaire which was distributed to 520 HIS students and 796 HS students in South Kalimantan. Data were analyzed by t-test to determine the significance of differences in satisfaction levels. The results found that online learning during the pandemic was carried out with various platforms, and there were no changes in the learning system: curriculum and syllabus. Online learning in South Kalimantan at the IHS/HS level is faced with problems with an internet connection, internet quota, student independence, learning design, and technical ability. The satisfaction of IHS and HS students in South Kalimantan with regard to learning is in the quite satisfactory category (average score of 2.9). The difference between the two types of education is significant 0.009, with a significance level of <0.05. Thus, H0 is rejected, and Ha is accepted.